Semantic Knowledge Base in Support of Activity Recognition in Smart Home Environments - Syafiq Abdull Sukor, Abdul; Zakaria, Ammar; Abdul Rahim, Norasmadi; Setchi, Rossi (International Journal of Engineering and Technology, 2018)
Activity recognition plays a major role in smart home technologies in providing services to users. One of the approaches to identify activity is through the use of knowledge-driven reasoning. This paper presents a framework of semantic activity recognition, which is used to support smart home systems to identify usersâ€™ activities based on the existing context. The framework consists of two main components: a semantic knowledge base and an activity recognition module. The knowledge base is represented using ontology and it is used to provide a semantic understanding of the environment in order to classify usersâ€™ patterns of activities. Experimental results show that the proposed approach can support the classification process and accurately infer usersâ€™ activities with the accuracy of 90.9%.Â Â